Mãos tecendo histórias de vida : memórias dos surdos sergipanos egressos do Instituto Nacional de Educação de Surdos (1944-1979) - Costa, Edivaldo da Silva (2018)
This thesis integrates the productions of the field of History of Special Education and the historiography of Sergipe, having as theoretical-methodological foundation the assumptions of Cultural History. He spoke on the subject of education of the sergipian deafs in the National Institute of Education of the Deaf (INES), the first school in Brazil, specialized for deaf people, to instruct, educate and professionalize this population. The general objective was to describe the educational and professional life trajectory of all the sergipian deafs who studied at the National Institute of Education of the Deaf (INES) in the decades of 1944 to 1979. For this purpose, the following specific objectives were elaborated: a) influence of the National Institute of Deaf Education in the school education and professional career of the sergipian deafs; b) to show educational aspects for the deaf in the management of Ana Rimoli de Faria Dória and Marino Gomes Ferreira; c) present the different modalities of communication and teaching methods for the deaf; d) highlight the actions of the public policies of the education of the deaf in the Governments of Juscelino Kubitschek de Oliveira and Emílio Garrastazu Médici; and e) to describe the life stories through the memory present in the narratives of the sergipian deafs graduates of INES. Life histories were collected from deaf deponents who graduated from the institution and from relatives. Period in which the first effective movements at the national level for the schooling of the Brazilian deaf appeared. In addition to the interviews, sources of documentary and iconographic nature were also analyzed. The conceptual framework adopted was based on the concepts of representation, appropriation, school culture, history and memory; the main authors who contributed to the understanding of the historical processes were Chartier, Julia, Halbwachs, Le Goff and Pollak; and in the area of the history of deaf education, Soares, Mattos, Souza, Rocha and Seixas. The thesis defended in this work was that even with all the institutional and methodological apparatus of INES and segregative character, based on oralism, initially aimed at rehabilitation, and later, for instruction, limited to primary education, training received in the INES represented for the sergipian deafs graduates the possibility of economic and professional independence. In order to concretize the analysis, there was an effort to understand the aspects related to the schooling process during the INES boarding school; the coexistence in the school space; professional workshops; civic parades; the first Eucharistic communion; sports activities and articulate language; the uniforms; school festivities; and career after INES. The reports of these experiences about education and professional career allowed the identification of nine sergipian deafs (five of whom are deceased) and it was possible to know not only the individual trajectories, but also the collective experiences in the school space. It was concluded that in spite of the primary schooling attended by the sergipian deafs at INES, the studies carried out contributed to their inclusion in the labor market and their economic and professional independence.________________________________________________________________________________________________________________________________